Influence Of Perceptions Of Price And Service Quality On Consumer Satisfaction (Survei Of Encep Cibeureum Tasikmalaya Building Store Consumers) - Apriani, Almi Dewi; Arisman, H Ari; Oktaviani, Nita Fauziah (Utami Publisher, 2024)
This research aims to determine the influence of price perceptions and service quality on consumer satisfaction (Survei on Consumers of the Encep Cibeureum Tasikmalaya Building Store). The method used in this research is causality through a survey approach, with the sample selected in this research being Consumers of the Encep Cibeureum Tasikmalaya Building Store, namely 100 respondents. The analytical tool used in this research is multiple regression using SPSS version 25. The results of the research show that Price Perception and Service Quality have a significant influence on Consumer Satisfaction at Encep Cibeureum Tasikmalaya Building Store Consumers. Partially, price perception has a significant influence on consumer satisfaction. Service Quality has a significant influence on Consumer Satisfaction at the Encep Cibeureum Tasikmalaya Building Store.